The Diversity and Geographic Distribution of Cultivable Bacillus-Like Bacteria Across Black Soils of Northeast China - Liu, Junjie; Cui, Xiao; Liu, Zhuxiu; Guo, Zhaokui; Yu, Zhenhua; Yao, Qin; Sui, Yueyu; Jin, Jian; Liu, Xiaobing; Wang, Guanghua (Frontiers in Microbiology, 2019)
Bacillus-like species are gram-positive bacteria, which ubiquitously in soils and some members of them are considered as beneficial microbes widely used in industry and agriculture. However, the knowledges related to their diversity and distribution patterns in soils is still rudimentary. In this study, a combined research method of using culture-dependent and high-throughput sequencing was subjected to investigate the composition and diversity of Bacillus-like bacterial communities across the black soil zone in northeast China. In total, 1,024,205 bacterial 16S rDNA sequences were obtained from 26 black soil samples, and all sequences were classified into order Bacillales. At genus level, 15 genera were detected with Bacillus, Paenibacillus, and Brevibacillus were three most abundant genera; At OTU level, although more than 2000 OTUs were obtained across all samples, but 33 OTUs were confirmed as the abundant species with relative abundance over 5% in at least one sample. Pairwise analysis showed that the diversity of Bacillus-like bacterial communities was significantly and positively correlated with soil total carbon contents and soil sampling latitudes, which suggested that a latitudinal gradient diversity of Bacillus-like bacterial communities existed in the black soil zone. The principal coordinates analysis revealed that the Bacillus-like bacterial communities was remarkably affected by soil sampling latitudes and soil total carbon content. In general, this study demonstrated that the distinct biogeographic distribution pattern of Bacillus-like bacterial communities existed in the black soil zone, which emphasis the strategy of local isolation and application of beneficial Bacillus-like strains is rather important in black soil agriculture development.